Diversidade funcional e estratégias adaptativas de algas perifíticas em planície de inundação. - Oliveira, Bárbara Dunck (2013)
This study emphasizes that syntheses on biodiversity should consider the functional aspect of the species towards better understanding of the processes involved in community ecology and ecosystem functioning. This study is the first to assess the functional diversity and the functional and taxonomic beta diversity of periphytic algae in floodplain. For this, periphytic algae were evalueted on natural substrates, in two consecutive years in floodplain lakes. In a first approach the environmental filters were tested as structuring the functional diversity of these communities in two hydrological periods. In consecutive approaches, the objectives aimed to evaluate the functional and taxonomic beta diversity of these communities, what was the relationship between them and their partitioned components, and if environmental dissimilarity of the lakes was related to the functional and taxonomic beta dissimilarity. For the entire thesis the functional matrix comprised four functional traits of the species, and was used for construction of functional dendrograms. The main patterns demonstrated by this study were: i) that higher values of periphytic algae functional diversity are related to high-water period and less impacted environments; ii) there is no evidence that environmental filters are structure for the periphytic algae functional diversity in floodplain, and that dispersion-restricting is an important factor in this structure; iii) the taxonomical and functional beta diversity of these organisms may reveal different patterns; iv) surprisingly high taxonomic beta diversity not reveals high functional beta diversity, because there is a large redundancy in functional traits among species, even between dissimilar lakes. That way, was proved the necessity of to incorporate functional approach in studies of periphytic algae, and is an incentive to continue the evaluation of the periphytic algae functional traits on floodplains and other aquatic ecosystems.